2017
DOI: 10.21577/0103-5053.20170192
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Biological Evaluation and Molecular Modeling Studies of Novel Eugenol Esters as Leishmanicidal Agents

Abstract: Leishmaniasis is a neglected pathology with a high incidence worldwide, and is a governmental health issue due to the increased morbidity and mortality associated with the disease and a scarce therapeutic arsenal. Cysteine proteases have been investigated as targets for new drugs because they are essential in the infectivity of the parasite during its interaction with the host and in its nutrition. This study aimed to identify compounds with leishmanicidal activity, by synthesis of compounds, in vitro evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Molecular dynamics (MD) simulations were used to validate the structural stability and conformational flexibility of a protein-ligand complex [44] , [66] . MD simulations provide powerful tools for the prediction of each atomic movement of protein, ligands, and physics governing interatomic interactions over a specific time [67] . To validate the structural stability and conformational flexibility protein ligands complex generated from the molecular docking study were subjected to 250 (ns) nanoseconds of MD simulations [68] .…”
Section: Methodsmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations were used to validate the structural stability and conformational flexibility of a protein-ligand complex [44] , [66] . MD simulations provide powerful tools for the prediction of each atomic movement of protein, ligands, and physics governing interatomic interactions over a specific time [67] . To validate the structural stability and conformational flexibility protein ligands complex generated from the molecular docking study were subjected to 250 (ns) nanoseconds of MD simulations [68] .…”
Section: Methodsmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations was used to validate the structural stability and conformational exibility of a protein-ligand complex [41]. MD simulations provide powerful tools for the prediction of each atomic movement of protein, ligands, and physics governing interatomic interactions over a speci c time [63]. To validate the structural stability and conformational exibility protein ligands complex generated from the molecular docking study were subjected to 250 (ns) nanoseconds of MD simulations [64].…”
Section: Molecular Dynamics (Md) Simulationmentioning
confidence: 99%
“…Bearing in mind the resistance to MTZ and its side effects, especially with higher doses, the control of blastocystosis constitutes a challenge. Investigation of the antiprotozoal activity of S. aromaticum essential oil against Leishmania by Coelho et al, [34] showed that eugenol component of S. aromaticum inhibits leishmanial cysteine proteases, which are vital in several aspects of protozoa life cycle [35] . Furthermore, a surface-located cysteine protease was shown to be involved in the pro-survival role of B. legumain subtype 7 [36] .…”
Section: S Aromaticum Essential Oil Inhibition Of Viabilitymentioning
confidence: 99%